Availability of essential medicines, progress and regional distribution in China: a systematic review and meta-analysis - Zhang, Miao; Zou, Kun; Liu, Zheng; Liu, Dan; Wang, Xiuli; Shi, Yuqing; Chen, Zhe; Cheng, Xiao; Lang, Bingchen; Li, Hailong; Zeng, Linan; Tang, Yong; et al. (Frontiers in Public Health, 2023)
Background: Essential medicines are the backbone of healthcare and meet the priority healthcare needs of the population. However, approximately one-third of the global population does not have access to essential medicines. Although China formulated essential medicine policies in 2009, the progress of availability of essential medicines and regional variations remains unknown. Therefore, this study was conducted to evaluate the availability of essential medicines, their progress, and regional distribution in China in the last decade. Methods: We searched eight databases from their inception to February 2022, relevant websites, and reference lists of included studies. Two reviewers selected studies, extracted data, and evaluated the risk of bias independently. Meta-analyses were performed to quantify the availability of essential medicines, their progress, and regional distribution. Results: Overall 36 cross-sectional studies conducted from 2009 to 2019 were included, with regional data for 14 provinces. The availability of essential medicines in 2015-2019 (28.1%, 95% confidence interval (CI): 26.4%-29.9%) was similar to that in 2009-2014 (29.4%, 95% CI: 27.5%-31.3%); lower in the Western region (19.8%, 95% CI: 18.1%-21.5%) than Eastern (33.8%, 95% CI: 31.6%-36.1%) and Central region (34.5%, 95% CI: 30.6%-38.5%); very low for 8 Anatomical Therapeutic Chemical (ATC) categories (57.1%), and low for 5 categories (35.7%) among all ATC groups. Conclusion: The availability of essential medicines in China is low compared with the World Health Organization goal, has not changed much in the last decade, is unequal across regions, and lacks data for half of provinces. For policy making, the monitoring system of the availability of essential medicines is to be strengthened to enable long-term surveillance, especially in provinces where the data has been missing. Meanwhile, Joint efforts from all stakeholders are warranted to improve the accessibility of essential medicines in China towards the universal health coverage target.